The Conflict of Planned Birth as Seen Jodi Picoult’s My Sister’s Keeper - Helmita Helmita; Sri Lestari (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This research is motivated by the existence of external and internal conflicts that are manifested by the author in the novel My Sister's Keeper by Jodi Picoult. The purpose of this research is to identify the external conflict experienced by Kate, analyze the inner conflict experienced by the characters Anna and Kate and the causes of external conflict and inner conflict in the novel My Sister's Keeper by Jodi Picoult. This method used in this research is descriptive qualitative. The data in this novel are excerpts of words, sentences related to the external conflict in Anna's character and the inner conflict of Anna and Kate's characters. The data collection techniques in this research were reading, marking data, recording and distinguishing the data collected based on external conflicts and inner conflicts in the novel My Sister's Keeper by Jodi Picoult. The results of this research indicate that in the novel My Sister Keeper by Jodi Picoult, Anna's external conflict is caused by her own family, especially her mother, the inner conflict between Anna and Kate's characters, namely, Id, Ego, and Superego. Anna and the causes of internal conflicts that are felt by Anna and Kate are individual differences, differences in cultural backgrounds and differences in interests between individuals.